Study on the Preparation of Cellulose Acetate Separation Membrane and New Adjusting Method of Pore Size - Wang, Jianming; Song, Hongchen; Ren, Longfei; Talukder, Md Eman; Chen, Shunquan; Shao, Jiahui (Membranes (Basel), 2021)
As a kind of eco-friendly (biodegradable) material and with a natural anti-fouling ability, cellulose acetate (CA) is more suitable for single-use membrane (especially in bioprocess). In this study, the method for preparing CA membrane by Vapor-assisted Nonsolvent Induced Phase Separation (VNIPS) was studied. The influences of ratio compositions (solid content, acetone/N,N-Dimethylacetamide ratio, glycerol/CA ratio) and membrane preparation conditions (evaporation time, evaporation temperature and humidity) on the microstructure and other properties were systematically evaluated. Results indicated that acetone/N,N-Dimethylacetamide ratio and glycerol/CA ratio had great influence on the cross-section structure of membranes. Additionally, the membrane with homogeneous sponge-like porous structure could be prepared stably within certain limits of ratios. Under the premise of keeping the content of other components fixed, the separation membrane with a full sponge pore structure can be obtained when the ratio of glycerol/CA is ≥2.5 or the acetone/solvent ratio is between 0.25 and 0.5. Evaporation time and temperature, humidity and other membrane preparation conditions mainly affected the surface morphology and the pore size. This kind of high-performance membrane with homogeneous sponge-like pore and controllable surface morphology could be potentially used for bioseparation processes.